2019
DOI: 10.1186/s12872-019-1016-4
|View full text |Cite
|
Sign up to set email alerts
|

Progression of coronary atherosclerotic plaque burden and relationship with adverse cardiovascular event in asymptomatic diabetic patients

Abstract: BackgroundThe heterogeneity of risk in patients with diabetes mellitus (DM) is acknowledged in new guidelines promulgating different treatment recommendations for diabetics at low cardiac risk. We performed a retrospective longitudinal follow-up study to evaluate coronary plaque progression and its impact on cardiac events in asymptomatic diabetic patients.MethodsData of 197 asymptomatic patients (63.1 ± 17 years, 60% males) with DM and suspected coronary artery disease (CAD) who underwent clinically indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Although implying pro-arrhythmogenic potential, studies showed rather reduced risk of triggered ventricular dysrhythmias in STZ model [ 4 , 5 ]. This is in line with certain evidence showing less tendency of diabetic hearts to ventricular arrhythmias regardless of pronounced risk of cardiovascular morbidity and mortality in diabetic patients [ 4 , 6 , 34 ] but it is contradictory to the impaired cardiac repolarization in DM [ 2 , 35 ] suggesting effective compensatory mechanisms. The main finding of our study in this model is the downregulation of HCN2 channel exclusively in ventricular myocardium possibly contributing to regulation of electric stability of diabetic ventricles.…”
Section: Discussionsupporting
confidence: 86%
“…Although implying pro-arrhythmogenic potential, studies showed rather reduced risk of triggered ventricular dysrhythmias in STZ model [ 4 , 5 ]. This is in line with certain evidence showing less tendency of diabetic hearts to ventricular arrhythmias regardless of pronounced risk of cardiovascular morbidity and mortality in diabetic patients [ 4 , 6 , 34 ] but it is contradictory to the impaired cardiac repolarization in DM [ 2 , 35 ] suggesting effective compensatory mechanisms. The main finding of our study in this model is the downregulation of HCN2 channel exclusively in ventricular myocardium possibly contributing to regulation of electric stability of diabetic ventricles.…”
Section: Discussionsupporting
confidence: 86%
“…To understand that the coronary atherosclerotic change is an important issue in clinical practice, it is well-known that diabetes has close association with the prevalence and severity of CCTA verified CAD progression [ 23 ]. Even asymptomatic diabetic patients experience plaque progression as well as evolution to overt or silent CAD, and an increase in the PV was reported to be associated with subsequent CV events [ 24 ]. In addition, the increased duration of diabetes combined with higher HbA1c levels deleteriously influences culprit-plaque characteristics among diabetic patients who suffered acute myocardial infarction [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even asymptomatic diabetic patients experience plaque progression as well as evolution to overt or silent CAD, and an increase in the PV was reported to be associated with subsequent CV events [24]. In addition, the increased duration of diabetes combined with higher HbA1c levels deleteriously influences culprit-plaque characteristics among diabetic patients who suffered acute myocardial infarction [25].…”
Section: Recent Investigations On the Longitudinal Assessment Of Coromentioning
confidence: 99%
“… 5 , 6 Serial assessment of coronary artery plaques through coronary CT angiography provides clinical information regarding the progression of disease and the risk of experiencing future adverse cardiovascular events. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%